Enabling cross-sectoral transformation for coastal climate adaptation in Europe: Four directions for interdisciplinary efforts - Kristof Tomej; Carla Garcia-Lozano; Josep Vila-Subiros; Alberto Innocenti; Emil Juvan; Olivier Le Pape; Niels Tobias Arnoldussen; Jonathan Verschuuren; Tim Taylor; Gesche Huebner; Nicola Tollin; Sebastian Mernild (Environmental Science & Policy, 2026)

Storm Frequency and Intensity in the Faroe Islands Between 1940 and 2024: A Method for Establishing a Storm Record Based on the ERA5 Reanalysis Data - Rico Kongsager; Daniel Krieger; Bárður A. Niclasen; Frauke Feser; Andreas Nyholm; Sebastian Mernild (International Journal of Climatology, 2025)
This comprehensive study establishes a detailed storm record for the Faroe Islands from 1940 to 2024 using ERA5 and NORA3 reanalysis data, as well as in situ observations. Over these 85 years, the Faroe Islands experienced 396 storms, averaging 4.8 yearly. The data revealed that storm events occur most years, with notable periods of heightened activity. The majority of storms were classified as stormy weather (20.8–24.4 m/s), with fewer (1.4 yearly) but significant occurrences of severe storms (≥ 24.5 m/s), with a higher number of severe storms in specific areas. Predominant wind directions from the southwest and west highlight the influence of Atlantic weather systems, with storms mainly occurring in the winter months. Comparing wind observations from Tórshavn with ERA5 data calibrated with the high‐resolution NORA3 reanalysis highlighted the accuracy and limitations of ERA5 in capturing storm events. While the calibrated ERA5 data provided reliable estimates of average wind speeds, it tended to smooth out fluctuations, underrepresenting the variability and intensity of extreme wind conditions. Applying a gust factor, derived from detailed observations, adjusted ERA5 wind speeds to reflect true conditions better. The study also demonstrated the utility of geostrophic wind speed records derived from pressure measurements to construct a long‐term storm activity index. A trend analysis reveals almost no discernible long‐term trend in frequency and intensity, indicating minimal change over time. Overall, this study emphasises the need for continued monitoring and refinement in storm identification and classification methods to improve the accuracy of storm event representations, crucial for the mitigation of severe storm impacts in the region.

The role of blocking circulation and emerging open water feedbacks on Greenland cold‐season air temperature variability over the last century - Thomas J. Ballinger; Edward Hanna; Richard J. Hall; J. Rachel Carr; Saber Brasher; Erich C. Osterberg; John Cappelen; Marco Tedesco; Qinghua Ding; Sebastian H. Mernild (International Journal of Climatology, 2021)
Substantial marine, terrestrial, and atmospheric changes have occurred over the Greenland region during the last century. Several studies have documented record‐levels of Greenland Ice Sheet (GrIS) summer melt extent during the 2000s and 2010s, but relatively little work has been carried out to assess regional climatic changes in other seasons. Here, we focus on the less studied cold‐season (i.e., autumn and winter) climate, tracing the long‐term (1873–2013) variability of Greenland's air temperatures through analyses of coastal observations and model‐derived outlet glacier series and their linkages with North Atlantic sea ice, sea surface temperature (SST), and atmospheric circulation indices. Through a statistical framework, large amounts of west and south Greenland temperature variance (up to r 2 ~ 50%) can be explained by the seasonally‐contemporaneous combination of the Greenland Blocking Index (GBI) and the North Atlantic Oscillation (NAO; hereafter the combination of GBI and NAO is termed GBI). Lagged and concomitant regional sea‐ice concentration (SIC) and the Atlantic Multidecadal Oscillation (AMO) seasonal indices account for small amounts of residual air temperature variance ( r 2

Greenland surface air temperature changes from 1981 to 2019 and implications for ice‐sheet melt and mass‐balance change - Edward Hanna; John Cappelen; Xavier Fettweis; Sebastian H. Mernild; Thomas L. Mote; Ruth Mottram; Konrad Steffen; Thomas J. Ballinger; Richard J. Hall (International Journal of Climatology, 2021)
We provide an updated analysis of instrumental Greenland monthly temperature data to 2019, focusing mainly on coastal stations but also analysing ice‐sheet records from Swiss Camp and Summit. Significant summer (winter) coastal warming of ~1.7 (4.4)°C occurred from 1991–2019, but since 2001 overall temperature trends are generally flat and insignificant due to a cooling pattern over the last 6–7 years. Inland and coastal stations show broadly similar temperature trends for summer. Greenland temperature changes are more strongly correlated with Greenland Blocking than with North Atlantic Oscillation changes. In quantifying the association between Greenland coastal temperatures and Greenland Ice Sheet (GrIS) mass‐balance changes, we show a stronger link of temperatures with total mass balance rather than surface mass balance. Based on Greenland coastal temperatures and modelled mass balance for the 1972–2018 period, each 1°C of summer warming corresponds to ~(91) 116 Gt·yr −1 of GrIS (surface) mass loss and a 26 Gt·yr −1 increase in solid ice discharge. Given an estimated 4.0–6.6°C of further Greenland summer warming according to the regional model MAR projections run under CMIP6 future climate projections (SSP5‐8.5 scenario), and assuming that ice‐dynamical losses and ice sheet topography stay similar to the recent past, linear extrapolation gives a corresponding GrIS global sea‐level rise (SLR) contribution of ~10.0–12.6 cm by 2100, compared with the 8–27 cm (mean 15 cm) “likely” model projection range reported by IPCC in 2019 (SPM.B1.2). However, our estimate represents a lower limit for future GrIS change since fixed dynamical mass losses and amplified melt arising from both melt‐albedo and melt‐elevation positive feedbacks are not taken into account here.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

The Andes Cordillera. Part III : glacier surface mass balance and contribution to sea level rise (1979–2014) - Sebastian H. Mernild; Glen E. Liston; Christopher Hiemstra; Ryan Wilson (International Journal of Climatology, 2017)
Glacier surface mass balance ( SMB ) observations for the Andes Cordillera are limited and therefore estimates of the SMB contribution to sea‐level rise are highly uncertain. Here (in Part 3), we simulate glacier surface meteorological and hydrological conditions and trends for the Andes Cordillera (1979/80–2013/14; 35 years), covering the tropical latitudes in the north down to the sub‐polar latitudes in the far south, including the Northern Patagonia Icefield ( NPI ) and Southern Patagonia Icefield ( SPI ). Surface meteorological conditions and heat‐ and mass‐transfer processes were simulated for all glaciers having an area equal to or greater than 0.5 km 2 . SnowModel – a fully integrated energy balance, blowing‐snow distribution, multi‐layer snowpack, and runoff routing model – was used to simulate glacier SMBs for the Andes Cordillera. The Randolph Glacier Inventory ( RGI ; v. 4.0) and NASA Modern‐Era Retrospective Analysis for Research and Applications ( MERRA ) products, downscaled in SnowModel , allowed us to conduct relatively high‐resolution (1‐km horizontal grid; 3‐h time step) simulations of glacier air temperature, precipitation, sublimation, evaporation, runoff, and SMB . These simulated glacier SMBs were verified against both independent direct observed annual glacier SMB and satellite gravimetry and altimetry derived SMB , indicating a good agreement. For Andes glaciers, the 35‐year mean annual SMB was found to be −1.13 m water equivalent (w.e.), while the cumulative SMB was −39.6 m w.e., which is equal to a cumulative SMB contribution of 3.4 mm sea‐level equivalent ( SLE ) (∼0.1 mm SLE per year). However, for both NPI and SPI , the mean SMB was positive (where likely calving explains why geodetic estimates are negative). For the Andes Cordillera, the simulated mean glacier‐specific runoff was 41 L s −1 km −2 , while for NPI and SPI it was 213 and 198 L s −1 km −2 , respectively, indicating available water resources from NPI and SPI .

The Andes Cordillera. Part IV: spatio‐temporal freshwater run‐off distribution to adjacent seas (1979–2014) - Sebastian H. Mernild; Glen E. Liston; Christopher Hiemstra; Andrew P. Beckerman; Jacob C. Yde; James McPhee (International Journal of Climatology, 2017)
The spatio‐temporal freshwater river run‐off pattern from individual basins, including their run‐off magnitude and change (1979/1980–2013/2014), was simulated for the Andes Cordillera west of the Continental Divide in an effort to understand run‐off variations and freshwater fluxes to adjacent fjords, Pacific Ocean, and Drake Passage. The modelling tool SnowModel/HydroFlow was applied to simulate river run‐off at 3‐h intervals to resolve the diurnal cycle and at 4‐km horizontal grid increments using atmospheric forcing from NASA Modern‐Era Retrospective Analysis for Research and Applications (MERRA) data sets. Simulated river run‐off hydrographs were verified against independent observed hydrographs. For the domain, 86% of the simulated run‐off originated from rain, 12% from snowmelt, and 2% from ice melt, whereas for Chile, the water‐source distribution was 69, 24, and 7%, respectively. Along the Andes Cordillera, the 35‐year mean basin outlet‐specific run‐off (L s −1 km −2 ) showed a characteristic regional hourglass shape pattern with highest run‐off in both Colombia and Ecuador and in Patagonia, and lowest run‐off in the Atacama Desert area. An Empirical Orthogonal Function analysis identified correlations between the spatio‐temporal pattern of run‐off and flux to the El Niño Southern Oscillation Index and to the Pacific Decadal Oscillation.

The Andes Cordillera. Part I: snow distribution, properties, and trends (1979–2014) - Sebastian H. Mernild; Glen E. Liston; Christopher A. Hiemstra; Jeppe K. Malmros; Jacob C. Yde; James McPhee (International Journal of Climatology, 2017)
Snow cover presence, duration, properties, and water amount play a major role in Earth's climate system through its impact on the surface energy budget. Snow cover conditions and trends (1979–2014) were simulated for South America – for the entire Andes Cordillera. Recent data sets and SnowModel developments allow relatively high‐resolutions of 3‐h time step and 4‐km horizontal grid increment for this domain. US Geological Survey's Global Multi‐resolution Terrain Elevation Data 2010 topography, Global Land Cover ( GlobCover ), Randolph Glacier Inventory (v. 4.0) glacier, and NASA modern‐era retrospective analysis for research and applications data sets were used to simulate first‐order atmospheric forcing (e.g. near‐surface air temperature and precipitation, including the fraction of precipitation falling as snow) and terrestrial snow characteristics (e.g. snow cover days, snow water equivalent depth, and snow density). Simulated snow conditions were verified against moderate‐resolution imaging spectroradiometer‐derived snow cover extent and 3064 individual direct observations of snow depths. Regional variability in mean annual air temperature occurred: positive trends in general were seen in the high Andes Cordillera, and negative trends at relatively lower elevations both east and west of the Cordillera. Snow precipitation showed more heterogeneous patterns than air temperature due to the influence from atmospheric conditions, topography, and orography. Overall, for the Cordillera, much of the area north of 23°S had a decrease in the number of snow cover days, while the southern half experienced the opposite. The snow cover extent changed ∼−15% during the simulation period, mostly between the elevations of ∼3000 and 5000 m above sea level (a.s.l.). However, below 1000 m a.s.l. (in Patagonia) the snow cover extent increased. The snow properties varied over short distances both along and across the Andes Cordillera.

The Andes Cordillera. Part II : Rio Olivares Basin snow conditions (1979–2014), central Chile - Sebastian H. Mernild; Glen E. Liston; Christopher A. Hiemstra; Jacob C. Yde; James McPhee; Jeppe K. Malmros (International Journal of Climatology, 2017)
Snow cover extent, duration, and properties were simulated (1979/1980–2013/2014) for the Rio Olivares Basin (548 km 2 ) in central Chilean Andes, in an effort to understand conditions and trends (linear) at a basin scale. The National Aeronautics and Space Administration Modern‐Era Retrospective Analysis for Research and Applications products, together with the snow modelling software package SnowModel allowed simulations of first‐order atmospheric forcings (mean annual air temperature ( MAAT ) and water‐equivalent precipitation) and terrestrial snow features (snow cover extent, duration, snow water‐equivalent depth, snow density, and runoff generated from snow melt). Simulated snow cover extent and depletion curves were verified against Moderate Resolution Imaging Spectroradiometer‐derived snow cover data. For the Rio Olivares Basin, MAAT was −2.9 ± 0.6 °C with a mean 0° isotherm at 3325 m a.s.l. The greatest temporal and spatial changes in temperature over the 35‐year period occurred in January and at the highest elevations, respectively. Mean annual precipitation was 1.86 ± 0.60 m w.e., indicating an increase in precipitation of ∼0.1 m w.e. 100 m −1 increase in elevation. On average, ∼90% of the basin precipitation fell as snow, varying from 70% at ∼2600 m a.s.l., to 95% at ∼4200 m a.s.l. In 20 out of 35 years the snow cover extent went to 0% (no basin snow cover) by end‐of‐summer (during March), and the snow duration increased on average by ∼10 days 100 m −1 increase in elevation. Approximately 85% of the basin outlet freshwater runoff originated from snowmelt, making snowmelt a dominant contributor to water resources. Snowmelt‐derived basin runoff was dominated by variability in snow precipitation rather than by variability in MAAT .

Greenland precipitation trends in a long‐term instrumental climate context (1890–2012): evaluation of coastal and ice core records - Sebastian H. Mernild; Edward Hanna; Joseph R. McConnell; Michael Sigl; Andrew P. Beckerman; Jacob C. Yde; John Cappelen; Jeppe K. Malmros; Konrad Steffen (International Journal of Climatology, 2015)
Here, we present an analysis of monthly, seasonal, and annual long‐term precipitation time‐series compiled from coastal meteorological stations in Greenland and Greenland Ice Sheet ( GrIS ) ice cores (including three new ice core records from ACT11D , Tunu2013, and Summit2010). The dataset covers the period from 1890 to 2012, a period of climate warming. For approximately the first decade of the new millennium (2001–2012) minimum and maximum mean annual precipitation conditions are found in Northeast Greenland (Tunu2013 c. 120 mm water equivalent (w.e.) year −1 ) and South Greenland (Ikerasassuaq: c. 2300 mm w.e. year −1 ), respectively. The coastal meteorological stations showed on average increasing trends for 1890–2012 (3.5 mm w.e. year −2 ) and 1961–2012 (1.3 mm w.e. year −2 ). Years with high coastal annual precipitation also had a: (1) significant high number of precipitation days ( r 2 = 0.59); and (2) high precipitation intensity measured as 24‐h precipitation ( r 2 = 0.54). For the GrIS the precipitation estimated from ice cores increased on average by 0.1 mm w.e. year −2 (1890–2000), showing an antiphase variability in precipitation trends between the GrIS and the coastal regions. Around 1960 a major shift occurred in the precipitation pattern towards wetter precipitation conditions for coastal Greenland, while drier conditions became more prevalent on the GrIS . Differences in precipitation trends indicate a heterogeneous spatial distribution of precipitation in Greenland. An Empirical Orthogonal Function analysis reveals a spatiotemporal cycle of precipitation that is linked instantaneously to the North Atlantic Oscillation and the Atlantic Multidecadal Oscillation and with an ∼6 years lag time response to the Greenland Blocking Index.

Coastal Greenland air temperature extremes and trends 1890–2010: annual and monthly analysis - Sebastian H. Mernild; Edward Hanna; Jacob C. Yde; John Cappelen; Jeppe K. Malmros (International Journal of Climatology, 2014)
We use observed air temperature data series from 14 meteorological stations in coastal Greenland (located all around the Greenland Ice Sheet) for 1960–2010, where long‐term records for five of the stations extend back to 1890, to illustrate the annual and monthly temporal and spatial distribution of temperature extremes, with the main focus on the latest decade 2001–2010 (2000s). We find that the 2000s had the highest number of mean annual air temperature ( MAAT ) warm extremes, and the 1890s the highest number of cold extremes, and that a high (low) positive North Atlantic Oscillation ( NAO ) Index equals a high number of cold (warm) extreme events. For the 2000s the number of warm extremes was significantly higher by around 50% than the number in the 1940s (the early twentieth century warm period): the latter being the decade with the second highest occurrence of MAAT warm extremes. Since 1960, based on MAAT the number of cold extremes has overall decreased on the decadal timescale, besides a peak in 1980s, while warm extremes have increased, leading to a higher occurrence of extremes (cold plus warm extremes): an almost similar pattern occurred for monthly mean temperatures and monthly mean daily maximum and minimum temperature datasets. Furthermore, a division of Greenland into east and west sectors shows that the occurrence of cold (warm) extremes was more pronounced in the East than in the West in the 1960s and 1970s (mid‐1980s to the 2000s).

Atmospheric and oceanic climate forcing of the exceptional Greenland ice sheet surface melt in summer 2012 - Edward Hanna; Xavier Fettweis; Sebastian H. Mernild; John Cappelen; Mads H. Ribergaard; Christopher A. Shuman; Konrad Steffen; Len Wood; Thomas L. Mote (International Journal of Climatology, 2014)
The NASA announcement of record surface melting of the Greenland ice sheet in July 2012 led us to examine the atmospheric and oceanic climatic anomalies that are likely to have contributed to these exceptional conditions and also to ask the question of how unusual these anomalies were compared to available records. Our analysis allows us to assess the relative contributions of these two key influences to both the extreme melt event and ongoing climate change. In 2012, as in recent warm summers since 2007, a blocking high pressure feature, associated with negative NAO conditions, was present in the mid‐troposphere over Greenland for much of the summer. This circulation pattern advected relatively warm southerly winds over the western flank of the ice sheet, forming a ‘heat dome’ over Greenland that led to the widespread surface melting. Both sea‐surface temperature and sea‐ice cover anomalies seem to have played a minimal role in this record melt, relative to atmospheric circulation. Two representative coastal climatological station averages and several individual stations in south, west and north‐west Greenland set new surface air temperature records for May, June, July and the whole ( JJA ) summer. The unusually warm summer 2012 conditions extended to the top of the ice sheet at Summit, where our reanalysed (1994–2012) DMI Summit weather station summer ( JJA ) temperature series set new record high mean and extreme temperatures in 2012; 3‐hourly instantaneous 2‐m temperatures reached an exceptional value of 2.2°C at Summit on 11 July 2012. These conditions translated into the record observed ice‐sheet wide melt during summer 2012. However, 2012 seems not to be climatically representative of future ‘average’ summers projected this century.

The influence of North Atlantic atmospheric and oceanic forcing effects on 1900–2010 Greenland summer climate and ice melt/runoff - Edward Hanna; Julie M. Jones; John Cappelen; Sebastian H. Mernild; Len Wood; Konrad Steffen; Philippe Huybrechts (International Journal of Climatology, 2013)
Correlation analysis of Greenland coastal weather station temperatures against the North Atlantic Oscillation (NAO) and the Atlantic Multidecadal Oscillation (AMO) indices for the summer season (when Ice Sheet melt and runoff occur) reveals significant temporal variations over the last 100 years, with periods of strongest correlations in the early twentieth century and during recent decades. During the mid‐twentieth century, temperature changes at the stations are not significantly correlated with these circulation indices. Greenland coastal summer temperatures and Greenland Ice Sheet (GrIS) runoff since the 1970s are more strongly correlated with the Greenland Blocking Index (GBI) than with the NAO Index (NAOI), making the GBI a potentially useful predictor of ice‐sheet mass balance changes. Our results show that the changing strength of NAOI–temperature relationships found in boreal winter also extends to summer over Greenland. Greenland temperatures and GrIS runoff over the last 30–40 years are significantly correlated with AMO variations, although they are more strongly correlated with GBI changes. GrIS melt extent is less significantly correlated with atmospheric and oceanic index changes than runoff, which we attribute to the latter being a more quantitative index of Ice Sheet response to climate change. Moreover, the four recent warm summers of 2007–2010 are characterised by unprecedented high pressure (since at least 1948—the start of the NCEP/NCAR reanalysis record) in the tropospheric column. Our results suggest complex and changing atmospheric forcing conditions that are not well captured using the NAO alone, and support theories of an oceanic influence on the recent increases in Greenland temperatures and GrIS runoff. Copyright © 2012 Royal Meteorological Society